한국 약용식물의 최종당화산물 생성저해활성 검색 (XII) - 최소진(So Jin Choi); 김영숙(Young Sook Kim); 김주환(Joo Hwan Kim); 김진숙(Jin Sook Kim) (생약학회지, 2015)
Advanced glycation end products (AGEs) have been implicated in diabetic complications. In this study, the inhibitory effect on AGEs formation of 156 Korean herbal medicines has been evaluated. Among them, 15 Korean herbal medicines were showed to have significant effect (IC50: <10 μg/ml) compared to positive reference, aminoguandine (IC50: 76.47±4.81 μg/ml). Especially, four herbal medicines, Alnus firma (leaves, IC50: 3.25±0.10 μg/ml), Juncus decipiens (whole plants, IC50: 4.30±0.44 μg/ml), Smilax china (stems, IC50: 3.55±0.21 μg/ml), and Vicia amoena (Aerial parts, IC50: 4.25±0.06 μg/ml) showed more potent inhibitory activity approximately 8-24 fold) than the positive control aminoguanidine.